(untitled) (Third Sector Social Economic Review, 2024)
The aviation sector comprises a dynamic work environment encompassing various professionals such as pilots, cabin crew, and ground service personnel. Employees in this sector often work long hours under intense pressure and frequently encounter stressful and uncertain situations. Therefore, it is crucial for aviation companies to provide various resources and support systems to enhance the psychological well-being of their employees. Building upon this premise, this study aims to investigate the regulatory role of mindfulness in the relationships between psychological capital and well-being among pilots, cabin crew, and ground service personnel working in Ankara’s aviation sector. Data gathered from 479 participants was meticulously analyzed using the SPSS 22 software. The findings reveal a significant positive relationship between psychological capital and psychological well-being. A key finding of the study is the identification that mindfulness plays a regulatory role in enhancing the link between psychological capital and psychological well-being. Consequently, these findings contribute significantly to the literature by expanding perspectives on psychological well-being and mindfulness concepts, thereby enhancing the understanding of psychological resilience and well-being among aviation sector employees. The study also provides theoretical and practical implications and recommendations for future research endeavors.